Rekonstruksi Pendekatan Hukum Berbasis Maqasid Syariah dalam Pembentukan Peraturan Perundang-Undangan di Indonesia - Abd. Rahman; Muhammad Afif; Zulfitriana Zulfitriana; Abdul Aziz Anwar; Andi Herawati; Azman Arsyad (Asian Journal of Islamic Studies and Da'wah, 2026)
The formation of laws and regulations in Indonesia is still dominated by a legal-positivist approach oriented toward procedure and formal validity, so it has not fully addressed the demands of substantive justice and public welfare. This condition is reflected in the continued existence of regulatory disharmony, overlapping norms, and the low effectiveness of legal implementation. This study aims to analyze the relevance of Maqasid Shariah as a substantive paradigm in the formation of laws and regulations and to formulate a maqasid-based legislative reconstruction model within the national legal system. This study uses a normative legal method with conceptual and statutory approaches. Data were obtained through library research covering laws and regulations, legal literature, scholarly articles, and relevant policy documents, then analyzed qualitatively using descriptive-analytical techniques. The results of the study show that the dominance of the legal-positivist approach in national legislation tends to place formal legality as the primary measure of legal success. In contrast, Maqasid Shariah as developed by Jasser Auda offers a legislative paradigm oriented toward public welfare, justice, protection of fundamental rights, and societal well-being. This study formulates a maqasid-based legislative model through three main stages, namely legislative planning, norm formulation, and regulatory evaluation, with four basic principles: orientation toward public welfare, protection of fundamental rights, inclusive public participation, and policy sustainability. The conclusion of the study affirms that the integration of Maqasid Shariah into the legislative process can strengthen the coherence between formal legality and substantive justice. The implications of this study contribute to the development of legislative theory and provide practical direction for lawmakers in improving regulatory quality and legal effectiveness in Indonesia.